AN ORDEAL OF SUFFERING IN TONI MORISON'S BELOVED - Bakhyaseema, K.P. (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Toni Morrison’s Beloved intricately weaves the legacy of slavery with the enduring psychological and emotional trauma it imparts on individuals and communities. This novel explores how trauma disrupts the capacity to articulate memory and identity, employing fragmented narrative structures and shifting perspectives to reflect the fractured experiences of the characters. The protagonist, Sethe, embodies the weight of historical and personal suffering, grappling with the haunting presence of her deceased daughter, Beloved, whose spirit demands remembrance and reconciliation. The narrative reveals how the repression of trauma prevents healing, as Sethe’s attempts to forget her harrowing past only deepen her alienation. Morrison employs stream-of-consciousness techniques and non-linear storytelling to mirror the disorientation caused by unresolved grief. This fragmented narrative style becomes a means of voicing silenced histories, challenging readers to engage with the complexities of memory and survival. Ultimately, Beloved underscores the transformative power of confronting trauma. By giving voice to the unspeakable, Morrison not only memorializes the atrocities of slavery but also affirms the resilience of those who endure. The novel becomes a profound meditation on the interdependence of memory, trauma, and narrative in the journey toward healing and self-reclamation